2011
DOI: 10.1111/j.1365-2516.2011.02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of female patients with inherited bleeding disorders in United States Haemophilia Treatment Centres

Abstract: SummaryInherited bleeding disorders are especially problematic for affected girls and women due to the monthly occurrence of menstrual periods and the effects on reproductive health. Although heavy menstrual bleeding (HMB) is the most common manifestation, females with inherited bleeding disorders (FBD) experience other bleeding symptoms throughout the lifespan that can lead to increased morbidity and impairment of daily activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 30 publications
3
59
2
Order By: Relevance
“…The incidence of HMB in the present study (50.0-53.3%) was concordant with the results of recent studies performed by Rae et al (29), Byams et al (30) and Kirtava et al (12) that reported incidence of 45.2, 51.7 and 44%, respectively. Regarding the study population, the women in the aforementioned studies were connected to hematology centers, as in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…The incidence of HMB in the present study (50.0-53.3%) was concordant with the results of recent studies performed by Rae et al (29), Byams et al (30) and Kirtava et al (12) that reported incidence of 45.2, 51.7 and 44%, respectively. Regarding the study population, the women in the aforementioned studies were connected to hematology centers, as in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Menorrhagia is the most common bleeding symptom in women of reproductive age with ARBDs [3][4][5][6][7][8], represents a very frequent cause of iron deficiency [1,3,6,9-12] and carries a high negative impact on the quality of life [2,7]. Furthermore, other frequent gynaecological problems, such as uterine fibroids, are more likely to be symptomatic because of the increased bleeding tendency.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other frequent gynaecological problems, such as uterine fibroids, are more likely to be symptomatic because of the increased bleeding tendency. In addition to menorrhagia, irregular menstrual cycles, breakthrough spotting, haemorrhagic ovarian cysts and endometriosis are other common gynaecological abnormalities reported in women with ARBDs [2,3,6]. With reference to the obstetric problems, bleeding may persist throughout pregnancy [12], especially when the haemostatic defect is severe.…”
Section: Introductionmentioning
confidence: 99%
“…The combined incidence of hemophilia A and B has been reported to be 1 in 5000 live male births. Rarely, hemophilia A is also observed in female children 6 . 80% of patients have hemophilia A and 60-70% of these have severe hemophilia A and 32% have moderate and mild hemophilia A 7,8 .…”
Section: Discussionmentioning
confidence: 99%